Python 3 and Machine Learning Using ChatGPT/GPT-4 - Campesato, Oswald (MLI Generative AI Series, 2024)
This book is designed to bridge the gap between theoretical knowledge and practical application in the fields of Python programming, machine learning, and the innovative use of ChatGPT-4 in data science.The book is structured to facilitate a deep understanding of several core topics.